TERT promoter hotspot mutations and their relationship with TERT levels and telomere erosion in patients with head and neck squamous cell carcinoma - Boscolo-Rizzo, Paolo; Giunco, Silvia; Rampazzo, Enrica; Brutti, Martina; Spinato, Giacomo; Menegaldo, Anna; Stellin, Marco; Mantovani, Monica; Bandolin, Luigia; Rossi, Marco; Del Mistro, Annarosa; Tirelli, Giancarlo; et al. (Journal of cancer research and clinical oncology, 2020)
Purpose To evaluate the prevalence of two recurrent somatic mutations (−124 C>T and −146 C>T) within the promoter of the gene encoding telomerase reverse transcriptase ( TERT ) as well as their relationship with TERT level, telomeres length, and outcome in patients with head and neck squamous cell carcinomas (HNSCCs). Methods We evaluate the prevalence of TERT promoter mutations, TERT levels, and telomere length in paired cancer tissue and adjacent mucosa (AM) in a series of HNSCCs. Results Cancer tissue and AM specimens from 105 patients were analyzed . Telomere length and TERT mRNA levels were estimated using real-time polymerase chain reaction. TERT promoter mutations were assessed using Sanger sequencing. Out of 105 cases, 101 were considered suitable for the analysis. TERT promoter harbored mutations in 12 tumors (11.9%), with −124 C>T and −146 C>T accounting for 83.3% and 16.7% of the alterations, respectively. No mutations were detected in AM samples. The prevalence of TERT promoter mutations was significantly higher in oral cavity SCCs (10 out of 27 tumors; 37%), and telomere length in AM was shorter in patients with tumors carrying TERT promoter mutations than in patients with unmutated TERT promoter cancers ( p = 0.023). TERT levels in tumor did not significantly differ according to the mutational status of TERT promoter. No significant association was found between TERT promoter status and overall survival. Conclusion TERT promoter mutations are most likely a late event in tumor development, occurring in a context of critically short telomeres, mostly in patients with oral cavity SCC. TERT levels, but not TERT promoter mutational status impact clinical outcome.